Farm transition and indigenous growth: The rise to medium- and large-scale farming in Ghana - Houssou, Nazaire; Asante-Addo, Collins; Chapoto, Antony (International Food Policy Research Institute, 2016)
This paper characterizes the transition from small-scale farming and the drivers of farm size growth among medium- and large-scale farmers in Ghana. The research was designed to better understand the dynamics of change in Ghana’s farm structure and contribute to the debate on whether Africa should pursue a smallholder-based or large-scale oriented agricultural development strategy. The results suggest a rising number of medium-scale farmers and a declining number of smallholder farmers in the country, a pattern that is consistent with a changing farm structure in the country’s agricultural sector. More important, findings show that the rise to medium- and large-scale farming is significantly associated with successful transition of small-scale farmers rather than entry of medium or large farms into agriculture, reflecting small-scale farmers successfully breaking through the barriers of subsistence agriculture into more commercialized production systems. The findings in this paper also suggest that some of the factors thought to be important for change in farm structure are no obstacle to farm size growth, even though they may foster transition. Notably, the results here diverge from the patterns observed in Zambia and Kenya, which indicate that the emergent farmers came mostly from the urban elite. Unfortunately, past and current policy discussions have not featured these emergent farmers sufficiently in the quest to transform agriculture in Ghana. Government should capitalize on these emergent farmers who have a demonstrated ability to graduate productively as it strives to address challenges in the smallholder sector.